KARAKTERISTIK FISIKOKIMIA DAN ORGANOLEPTIK KERUPUK SUBTITUSI SUSU DAN TEPUNG TAPIOKA DENGAN METODE CAIR - Haryati, Sri; Sudjatina, Sudjatina; Sani, Elly Yuniarti (Jurnal Pengembangan Rekayasa dan Teknologi, 2019)
Milk is one type of beverage that has great benefit to health. Milk is a consumable ingredient that must be given to babies to support their growth and development. In general, milk is used more for ingredients of beverage products, but with culinary creativity, we can also use milk ingredients for processed food products that are non-sweetness. . One that will be tried is the making of milk crackers. Dairy products in the form of crackers have a savory and crispy taste and as food ingredients they are quite unique and interesting, so research needs to be done. This study aims to determine the physicochemical and organoleptic characteristics of milk crackers derived from liquid milk substitute and tapioca flour with liquid methodThe experimental design used was a completely randomized design (CRD) of one factor namely liquid milk substitution and tapioca flour with a liquid method with 4 treatments and 5 replications. treatment as follows: P1: Milk 25 g: Tapioca flour: 75 g, P2: Milk 30 g: tapioca flour 70 g, P3: Milk 35 g: tapioca flour: 65 g, P4: milk 40 g: tapioca flour 60 g, If there is a real effect, then a further test with an Honestly Real Difference Test is carried out with a test level of 5%.The results showed that substitution of liquid milk and tapioca flour, in the manufacture of milk crackers with liquid method had a significant effect (p
Keywords: Crackers; liquid milk; tapioca flour